Comprehensive School Physical Activity Program Policies and Practices Questionnaire (CSPAP-Q). Issue 1 (2nd January 2021) - Stoepker, Peter; Dauenhauer, Brian; Carson, Russell L.; Moore, Justin B.
ABSTRACT: Purpose : The Comprehensive School Physical Activity Program (CSPAP) model has recently been adopted as a national framework for physical activity (PA) promotion in schools. As a result, there is a need to develop an instrument to help leaders of PA measure policies and practices across the five component areas of a CSPAP. To address this gap, our team systematically developed and assessed the psychometric properties of the CSPAP-Q, an instrument designed to assess school policies and practices related to the five components of CSPAP. Methods : The instrument development process began by reviewing existing school health and PA surveys. The Delphi method was then used to evaluate face and content validity through expert feedback. Thirty-eight physical education teachers completed the CSPAP-Q twice over a 14-day period to further establish validity and to assess test-retest reliability. Results : In total, 117 items were identified for the initial review. Upon completion of expert feedback, 22 items were eliminated and 66 items were revised. After reliability testing, three additional items were eliminated due to low test-retest agreement levels (Kappa <.40; non-significant χ 2 ). Ninety-two items were retained in the final version of the CSPAP-Q and kappa values indicated moderate to substantial agreement among items. Conclusions : After validity and reliability testing, results suggest that the CSPAP-Q is a valid and reliable tool for assessing policies and practices related to CSPAP.